1987
DOI: 10.1016/0014-5793(87)81126-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soluble forms of NCAM

Abstract: Neural cell adhesion molecule (NCAM) has been described as a family of membrane glycoproteins. However, soluble NCAM immunoreactivity has long been recognized. We here show that soluble NCAM is composed of two quantitatively major polypeptides of M r 180 000 and 115 000 and two minor components of M r 160 000 and 145 000. Soluble NCAM was immunochemically identical to membrane NCAM, was polysialylated and carried the HNK‐1 epitope. It only constituted 0.8% of total NCAM in newborn rat brain. Soluble NCAM appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 15 publications
2
16
0
1
Order By: Relevance
“…The sizes of the soluble 115 kD NCAM ectodomain and 30 kD membraneassociated (Buttner et al, 2004) fragments resulting from PV-induced shedding were in accord with NCAM fragments identified in brain (Bock et al, 1987(Bock et al, , 1988Nybroe et al, 1989;Krog et al, 1992) and cerebrospinal fluid (Krog et al, 1992). The size of the soluble fragment suggested that proteolytic cleavage occurred at a juxtamembrane site of NCAM140 located between the fifth Ig-like domain and the transmembrane segment.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The sizes of the soluble 115 kD NCAM ectodomain and 30 kD membraneassociated (Buttner et al, 2004) fragments resulting from PV-induced shedding were in accord with NCAM fragments identified in brain (Bock et al, 1987(Bock et al, , 1988Nybroe et al, 1989;Krog et al, 1992) and cerebrospinal fluid (Krog et al, 1992). The size of the soluble fragment suggested that proteolytic cleavage occurred at a juxtamembrane site of NCAM140 located between the fifth Ig-like domain and the transmembrane segment.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, a %115 kD band representing the soluble NCAM140 ectodomain appeared on blots of the conditioned media from pervanadate-stimulated cells using -NCAM-ECD antibodies ( Fig. 1, PV lower panel), and is the reported size of the NCAM ectodomain (Bock et al, 1987;Nybroe et al, 1989;Krog et al, 1992;Todaro et al, 2004). The 115 kD NCAM fragment was not present in conditioned media from untreated or PMA-treated cells.…”
Section: Cleavage Of the Ncam140 Ectodomain Is Induced By Pervanadatementioning
confidence: 88%
“…1). This exon contains a stop-codon thereby producing a truncated form of the extracellular part of NCAM with a M r around 115 kD (14,15). Soluble NCAM also exists in a ''shedded'' form.…”
Section: Isoforms Of Ncammentioning
confidence: 99%
“…Although NCAM is expressed transiently in various embryonic structures, the H-or Lform of NCAM is found predominantly in neurons and glial cells,4 in muscle," in the adrenal medulla," pheochromocytoma,'3 neuroblastoma cell^,'^,'^ anterior pituitary," pancreatic islets,17 developing kidney,18,19 Wilms tumor," and small cell lung cancer (SCLC) cell line^. '^,^^ The a- (2,8)-PSA-rich NCAM (NCAM-H) is recognized by a monoclonal antibody Mab 735," which also detects the SCLC cluster 1 (SC-1) antigens on SCLC cells, as shown recently by Moolenaar et alI5 In this study, we took a newly developed enzyme immunoassay that includes, aside from another NCAM-specific antibody, the monoclonal antibody Mab 735. To assess the value of NCAM as a possible tumor marker for patients with SCLC, we examined the sera of 221 patients with histologically confirmed SCLC in two prospective multicenter trials and compared the results with the expression of neuron-specific enolase (NSE), a rather specific and sensitive tumor marker for SCLC.…”
mentioning
confidence: 99%